HUBUNGAN TINGKAT KECEMASAN IBU SERTA DUKUNGAN KELUARGA DENGAN KELANCARAN PEMBERIAN ASI PADA BAYI DIRUANG PERINATOLOGI RS - Ana Mundhawaroh; Kurnia Wijayanti; Herry Susanto (Yayasan Healing and Healthcare Education, 2026)
Breastfeeding is a basic need for babies that plays an important role in supporting growth and development and immunity, especially for babies who are treated in the perinatology room. However, in these conditions, the smoothness of breastfeeding often faces various obstacles. One of the influential factors is maternal anxiety, which arises from the condition of the baby's illness, separation of mother and baby, postpartum pain, and the mother's concern about the mother's ability to produce breast milk. Objective: This study aims to determine the relationship between maternal anxiety levels and family support with the smoothness of breastfeeding in the perinatology ward of Sari Asih Hospital, Serang. Method: Quantitative research with a cross-sectional design involving 81 respondents, mothers of infants, selected using a purposive sampling technique. The research instrument used a questionnaire. Data analysis used the chi-square statistical test. Results: The results of univariate analysis showed that the majority of mothers in the perinatology ward of Sari Asih Hospital, Serang experienced irregular breastfeeding (53.1%), experienced moderate anxiety (49.4%), and had moderate family support (38.4%). The results of the bivariate analysis showed that anxiety factors (p: 0.000) and family support (p: 0.000) had a significant relationship with the smoothness of breastfeeding. Conclusion: There is a relationship between anxiety levels and family support with the smoothness of breastfeeding.